OCT-based vulnerable plaque features and MACE prediction in premature coronary artery disease - Liu, Jiabao; Meng, Haoyu; Chen, Leilei; Wang, Liansheng; Xu, Jiayang (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis study aimed to systematically analyze coronary plaque characteristics in patients with premature coronary artery disease (PCAD) using optical coherence tomography (OCT) and clarify their associations with clinical risk factors and major adverse cardiovascular events (MACE).MethodsA total of 224 patients (men ≤55 years, women ≤65 years) with suspected or confirmed CAD who underwent coronary angiography and OCT at the First Affiliated Hospital of Nanjing Medical University between February 2022 and February 2024 were enrolled. Among them, 142 were diagnosed with PCAD (observation group), and 82 had coronary stenosis <50% (control group). Baseline clinical data, risk factors, and OCT-derived plaque features were collected. Patients were followed for 12 months to record MACE. Statistical analyses included independent t-tests, chi-square tests, and multivariate Cox regression.ResultsThe PCAD group exhibited significantly higher prevalence rates of hypertension (63.38% vs. 47.56%), smoking (30.28% vs. 17.07%), and diabetes (19.72% vs. 8.54%), along with elevated total cholesterol (4.89 ± 1.41 vs. 4.41 ± 1.32 mmol/L), LDL-C (2.91 ± 0.98 vs. 2.51 ± 0.72 mmol/L), and lipoprotein(a) (50.2 ± 28.4 vs. 30.5 ± 18.7 mg/dl) compared to controls (all p < 0.05). OCT analysis revealed higher vulnerability in PCAD plaques, characterized by thinner fibrous caps (150.16 ± 82.71 vs. 250.71 ± 123.53 µm, p < 0.01), larger lipid arc (93.21 ± 36.43° vs. 60.10 ± 24.46°, p < 0.01), increased macrophage infiltration (19.01% vs. 4.87%, p < 0.01), and more intraplaque microchannels (14.79% vs. 8.53%, p < 0.05). During follow-up, MACE incidence was significantly higher in the PCAD group (12.68% vs. 3.70%, p < 0.01). Multivariate Cox regression identified thin-cap fibroatheroma (HR = 2.95), lipid arc ≥180° (HR = 2.61), macrophage infiltration (HR = 1.98), plaque rupture (HR = 2.82), and thrombosis (HR = 2.30) as independent predictors of MACE.ConclusionPatients with PCAD demonstrate distinct coronary plaque vulnerability features closely associated with metabolic and lifestyle-related risk factors. OCT enables precise identification of high-risk plaques, providing critical insights for early intervention and risk stratification to mitigate acute cardiovascular events.